The sugar protocol: an appraisal - Thomas Koch (Intereconomics, 1989)
A key issue in the talks on the fourth Lomé Convention is the demand of some Caribbean and Central American nations to join the ACP group, so as to benefit from the preferential treatment and financing facilities it enjoys. A specific concern is accession to the Sugar Protocol appended to the Lomé Agreement. The following article deals with the form and developmental implications of this protocol.
Keywords: 330; Lomé IV